A systematic review of the effects of increasing arachidonic acid intake on PUFA status, metabolism and health-related outcomes in humans. Issue 11 (27th May 2019) - Calder, Philip C.; Campoy, Cristina; Eilander, Ans; Fleith, Mathilde; Forsyth, Stewart; Larsson, Per-Olof; Schelkle, Bettina; Lohner, Szimonetta; Szommer, Aliz; van de Heijning, Bert J. M.; Mensink, Ronald P.
Abstract: We conducted a systematic review of randomised controlled trials (RCT) of increased intake of arachidonic acid (ARA) on fatty acid status and health outcomes in humans. We identified twenty-two articles from fourteen RCT. Most studies were conducted in adults. These used between 80 and 2000 mg ARA per d and were of 1–12 weeks duration. Supplementation with ARA doses as low as 80 mg/d increased the content of ARA in different blood fractions. Overall there seem to be few marked benefits for adults of increasing ARA intake from the typical usual intake of 100–200 mg/d to as much as 1000 mg/d; the few studies using higher doses (1500 or 2000 mg/d) also report little benefit. However, there may be an impact of ARA on cognitive and muscle function which could be particularly relevant in the ageing population. The studies reviewed here suggest no adverse effects in adults of increased ARA intake up to at least 1000–1500 mg/d on blood lipids, platelet aggregation and blood clotting, immune function, inflammation or urinary excretion of ARA metabolites. However, in many areas there are insufficient studies to make firm conclusions, and higher intakes of ARA are deserving of further study. Based on the RCT reviewed, there are not enough data to make any recommendations for specific health effects of ARA intake.